The Disclosure of Replacement Cost Accounting Data and Its Effect on Transaction Volumes: A Comment. - Freeman, Robert N. (The Accounting Review, 1981)
Abstract The article presents the author comments on the paper "The Disclosure of Replacement Cost Accounting Data and Its Effect on Transaction Volumes," by Byung T. Ro that was published in one of the previous issues of the journal "The Accounting Review." The intensity of investor demand for and their possible reaction to replacement cost (RC) disclosures as a supplement to traditional financial reports are continuing issues in the accounting literature, both professional and academic. According to the paper, a typical means of isolating the effects of firm-specific disclosures is to compare differential investor actions between a portfolio of firms disclosing the information and a matched sample of firms not disclosing the information. The author state that since the set of RC disclosure firms is effectively the set of "large" firms whose securities are publicly traded, it is clear that a control group matched on firm size is not available. If security returns and volume vary systematically with firm size, Ro's matched pair design will not allow for any direct conclusions regarding the effect of RC data.